Investigating the fit of a model for students’ understanding of fractions in a Norwegian context - Gustavsen, Trond Stølen; Imenes, Olav Gravir (NOMAD Nordic Studies in Mathematics Education, 2019)
To capture the complexity of students’ understanding of fractions, a model linking part-whole to the subconstructs ratio, operator, quotient and measure has been proposed. We ask if this model is compatible with students’ achievements in a Norwegian context. Responses from 638 students were analysed using structural equation modelling (SEM), and a good fit of the model was obtained after removing the ratio subconstruct. In particular, part-whole is seen to be important for operator, quotient and measure. Using qualitative analysis of interviews, we found reasoning associated with ratio, with a weak link to the part-whole subconstruct.